Impact of Caregiver Incentives on Child Health: Evidence from an Experiment with Anganwadi Workers in India - Prakarsh Singh; William A. Masters (Institute for the Study of Labor (IZA), 2016)
This paper provides evidence of effectiveness for performance pay among government caregivers to improve child health in India. In a controlled study of 160 daycare centers serving over 4,000 children, we randomly assign individual workers to receive either fixed bonuses or incentive payments based on the weight-for-age nutritional status of children in their care, and also collect data from a control group receiving only their standard salary. Mothers of children in all three study arms receive nutrition information. We find that performance pay reduces the prevalence of underweight by about 5 percentage points over 3 months, and height improves by about one centimeter. Impacts are sustained in the medium term when incentives are renewed but fade when they are discontinued. Fixed bonuses lead to smaller effects. Both treatments appear to improve worker effort and communication with mothers, who in turn feed a more calorific diet to their children at home.
Keywords: O1; I1; M5; 330; performance pay; incentives; malnutrition; undernutrition; underweight; child development; child health; Anganwadis; ICDS; nutrition